A Saudi Woman with Ceftriaxone Induced Fixed Drug Eruption - Rehab Y. Al-Ansari; Leena Abdulrahman Almuhaish; Khaled Abdullah Hassan; Tawasoul Fadoul; Alexander Woodman (Hindawi Limited, 2024)
Background. A fixed drug eruption (FDE) is an immunological cutaneous adverse reaction, classified as a cutaneous adverse drug reaction (CADR) and characterized by well-defined lichenoid lesions that occur at the same site each time. Ceftriaxone is a third-generation antibiotic of cephalosporin antibiotics of the beta-lactam antibiotic family, which has typical in vitro activity against many Gram-negative aerobic bacteria. This is the first clinical case from Saudi Arabia and the fifth in the world to document a woman's experience with recurrent FDE after repeated ceftriaxone use. Case Report. A 25-year-old Saudi woman with a known case of sickle cell anemia (SCA) with a history of avascular necrosis of the right hip after replacement was hospitalized with a pain crisis triggered by an upper respiratory tract infection. The patient denied having a history of allergy previously. Due to fever, leukocytosis, and active follicular tonsillitis, ceftriaxone was started. However, a few hours later she developed lip edema and a fixed drug eruption measuring 7 × 11 cm on the left side of her back. The lesion reformed over a hyperpigmented lesion (4 × 8 cm) that the patient did not report upon initial examination. It turned out that this was due to the intravenous administration of ceftriaxone, a year ago in another hospital. An allergy to ceftriaxone was considered, and steroids and antihistamines were started. The case was labeled as ceftriaxone induced FDE. Conclusion. Ceftriaxone induced FDE is an uncommon type of allergic reaction that has been reported infrequently. Understanding this condition and the mechanism by which FDE becomes recurrent with the same previous fixed lesion is of great importance for both academic and future research purposes.